Pengembangan Media Pembelajaran Anti Radikalisme untuk Siswa SMP di Kota Kediri melalui Media Komik - Yunita Dwi Pristiani; Siska Nurazizah Lestari (International Consortium of Education and Culture Research Studies, 2019)
Religious radicalism lately become talks in the national levels. Radicalism and Terrorism movement generally done by young people (Children), even students who are still in junior high school.This phenomenon make us, as parents and educators concerned, at once want to try hard prevent it. This study uses research and development approach, with research media education development developed by Borg and Gall. The purpose of this research is developing anti-radicalism learning media for PPKn Learning in Junior High School through comic media. The urgency of this research is to add references for PPKn teachers, in the use of learning media, especially in preventing radicalism, and inculcate correct understanding of religious, having state and prevent wrong understanding about state understanding.